A study of teak wood quality from community forests in Gunungkidul II. Growth-stress measurement - Sri Nugroho Marsoem; Vendy Eko Prasetyo; Joko Sulistyo; Ganis Lukmandaru (Jurnal Ilmu Kehutanan)
Trees containing large growth stresses, leads to significant losses due to split, checked and also warped. The variation of growth-stress in teak trees grown in the three community forest sites of Gunungkidul regency was observed. The released strain levels were also discussed in relation to the growth-rate and specific gravity. The strains released in the longitudinal and tangential directions were measured by the strain-gauge method. The values of longitudinal released strain at the periphery of the stem were ranged from -130.5 to -999.5 µå whereas tangential released strain were from -103 to 1411.5 µå. Some high values of longitudinal released strain indicated the presence of tension wood. Further, intra-tree variation of growth stress showed no particular tendencies among the samples. There were significant differences in the longitudinal strain as samples from Nglipar site showed the highest amounts (-628.25 + -223.73 µå). However, no significant correlation was found between the values of released strains with the growth-rate and specific gravity. The radial distributions of internal residual-stress were varied among the individuals which some trees exhibited steeper released strain gradients. Thus, it is important to reduce the gradient from pith to periphery of released-strain patterns to prevent the defect related to the growth stresses.